Combination of Markov and MultiDamping Techniques for Web Page Ranking (International Journal of Engineering and Computer Science, 2014)
Web page Re-ranking has been widely used to reduce the access latency problem of the Internet. However, if most prefetched web pages are not visited by the users in their subsequent accesses, the limited network bandwidth and server resources will not be used efficiently and may worsen the access delay problem. Therefore, it is critical that we have an accurate re-ranking method during prefetching. The technique like Markov models have been widely used to represent and analyze user‘s navigational behavior. One more technique is multidamping which utilize the stochastic matrix for the ranking of the pages. This paper give new algorithm for the page ranking different featurea combination of the markov as well as the multidamping method.